Pelayanan Publik Melalui E-Klampid dalam Mewujudkan Administrasi Kependudukan Berbasis Good Governace di Kota Surabaya - Aldi Pratama; Agus Sukristyanto; Yusuf Hariyoko (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2022)
Public service is a form of activity that is sought to assist service needs that refer to the laws and regulations for citizens and residents in the form of services, goods, or administrative services that have been provided by the public service providers. The government is obliged to carry out public services optimally based on law number 25 of 2009 article 1 paragraph 1 which explains that public service is a form of activity carried out by the government to fulfill the basic rights of its citizens. Therefore the provision of public services is required to be carried out in an optimal manner. optimal. One of the efforts to form public services held by the government is in the field of population administration. As a government agency in charge of providing all population administration services, especially for the Surabaya area. In developing a smart city using e-governance, it is none other than the Surabaya city government, especially the Surabaya City Civil Registration Department, which aims to provide better and excellent public services and provide convenience in interacting with the community. There is a need for reform which is intended to improve and even improve the quality, efficiency, and effectiveness of public service delivery. Through these reforms, systems, methods, and technologies will be created that can reduce costs, shorten service time, and cut bureaucracy. This study aims to determine the application of e-klampid in realizing good governance in the city of Surabaya and to find out the inhibiting and driving factors for e-klampid online. The research method applied in this study is a qualitative method. The results of his research refer to the four indicators of good governance, namely community participation, transparency, supremacy, effectiveness and efficiency.